IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) PADA LEMBAGA PENDIDIKAN DASAR DI INDONESIA: STUDI KASUS DI SD PLUS MELATI SAMARINDA - Anata Rifiyyah; Bahrani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of Total Quality Management (TQM) in primary education institutions through a case study at SD Plus Melati Samarinda. TQM is a managerial approach that emphasizes the participation of all organizational elements in the process of continuous quality improvement. This research uses a qualitative method with a case study design. Data collection techniques included observation, in-depth interviews, and documentation. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and verification. The results showed that TQM principles had been implemented at SD Plus Melati through leadership commitment, staff and teacher involvement, continuous training, and an internal quality evaluation system. However, challenges such as limited resources and resistance to change still exist. TQM implementation has contributed to improving the quality of educational services and stakeholder satisfaction.